Synthesis of potentially bioactive PABA-related N-(aminoalkyl)lactamic amino acids and esters via selective SNAr reactions - Goncalves, Renato S. [UNESP]; Abdelnur, Patricia V.; Santos, Vanessa G.; Simas, Rosineide C.; Eberlin, Marcos N.; Magalhaes, Alvicler; Perez Gonzalez, Eduardo R. [UNESP] (Springer, 2011)
Potentially bioactive N-(aminoalkyl)lactamic amino acids and esters were synthesized in satisfactory to good yields by SNAr reactions of aromatic acids with N-(3-aminopropyl)lactams followed by esterification with tertiary amino alcohols. The addition-elimination SNAr mechanism was confirmed by NMR and MS measurements.
Keywords: PABA derivatives; Lactams; Potential bio-activity; SNAr reaction